2015
DOI: 10.1007/s00411-015-0605-6
|View full text |Cite
|
Sign up to set email alerts
|

Proton-induced direct and indirect damage of plasmid DNA

Abstract: Clustered DNA damage induced by 10, 20 and 30 MeV protons in pBR322 plasmid DNA was investigated. Besides determination of strand breaks, additional lesions were detected using base excision repair enzymes. The plasmid was irradiated in dry form, where indirect radiation effects were almost fully suppressed, and in water solution containing only minimal residual radical scavenger. Simultaneous irradiation of the plasmid DNA in the dry form and in the solution demonstrated the contribution of the indirect effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 44 publications
1
54
0
Order By: Relevance
“…In this study, we validate TOPAS-nBio by comparing to a previous Monte Carlo study predicting strand breaks in a simple linear DNA segment for several particles types [11] and an experimental study measuring the occurrence of strand breaks within a DNA plasmid from incident protons [12]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we validate TOPAS-nBio by comparing to a previous Monte Carlo study predicting strand breaks in a simple linear DNA segment for several particles types [11] and an experimental study measuring the occurrence of strand breaks within a DNA plasmid from incident protons [12]. …”
Section: Methodsmentioning
confidence: 99%
“…The interactions of protons within the simple plasmid were simulated and compared to the experimental data from Vyšín et al [12]. In the experimental study, SSB and DSB yields in DNA plasmids after proton irradiation were measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly accepted that nanosize lesions, also called complex damages, are the most lethal for the cells. 23 In this work, we quantified the efficacy of 3 nm platinum (Z=78) and 5 nm gadolinium (Z=64) based NPs to amplify nanosize lesions upon fast proton irradiation. The plasmid pBR322 was used as a molecular probe to quantify simple and complex damages in biomolecules.…”
mentioning
confidence: 99%
“…The mass per square centimetre quantities used for determining density of dry DNA films are similar to those often used in irradiation studies [57], therefore the lower value should be used in future studies. Furthermore, since it was shown that there is a strong dependence of the sample composition on DNA film formation and thus on its density, interferometric method will be important in characterizing particle interactions with DNA films and the dose dependence [119]. The result presented here also indicates that depending on the film preparation method, i.e.…”
Section: Discussionmentioning
confidence: 51%